El sistema político y movimientos indígenas: el caso del EZLN - Mercado Maldonado, Asael (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The present article analyzes the links of the EZLN with the wretched situation in which million aborigens are in Mexico against the ingobernability neoliberal. We present possible solutions to the conflict EZLN, and summarize the achievements reached by the ethnic groups as for democracy inside the Mexican state.
Keywords: EZLN; Aborigens; Conflict; Ethnicity; Democracy